Nitrate dynamics in natural plants: insights based on the concentration and natural isotope abundances of tissue nitrate - Liu, Xue-Yan; Koba, Keisuke; Makabe, Akiko; Liu, Cong-Qiang (Frontiers in Plant Science, 2014)
The dynamics of nitrate (NO3-), a major nitrogen (N) source for natural plants, has been studied mostly through experimental N addition, enzymatic assay, isotope labeling, and genetic expression. However, artificial N supply may not reasonably reflect the N strategies in natural plants because NO3- uptake and reduction may vary with external N availability. Abrupt application and short operation times, field N addition, and isotopic labeling hinder the elucidation of in situ NO3--use mechanisms. The concentration and natural isotopes of tissue NO3- can offer insights into the plant NO3- sources and dynamics in a natural context. Furthermore, they facilitate the exploration of plant NO3- utilization and its interaction with N pollution and ecosystem N cycles without disturbing the N pools. The present study was conducted to review the application of the denitrifier method for concentration and isotope analyses of NO3- in plants. Moreover, this study highlights the utility and benefits of these parameters in interpreting NO3- sources and dynamics in natural plants. We summarize the major sources and reduction processes of NO3- in plants, and discuss the implications of NO3- concentration in plant tissues based on existing data. Particular emphasis was laid on the regulation of soil NO3 - and plant ecophysiological functions in interspecific and intra-plant NO3- variations. We introduce N and O isotope systematics of NO3- in plants and discusse the principles and feasibilities of using isotopic enrichment and fractionation factors; the correlation between concentration and isotopes (N and O isotopes: δ18O and ∆17O); and isotope mass-balance calculations to constrain sources and reduction of NO3- in possible scenarios for natural plants are deliberated. Finally, we construct a preliminary framework of intraplant δ18O-NO3- variation, and summarize the uncertainties in using tissue NO3- parameters to interpret plant NO3- utilization.